Self-Discharging and Corrosion Problems in Vanadium Redox Flow Battery - Dena Hendriana; Mochamad Hamdan Aziz; Yohanes Acep Nanang Kardana; Muhamad Lutfi Rachmat; Gembong Baskoro; Henry Nasution (Reaktor, 2022)
Vanadium redox flow battery (VRFB) has a potential for large energy storage system due to its independence of energy capacity and power generation. VRFB is known to have challenges of high price, corrosion problem and lower energy efficiency. In this work, VRFB prototype with all components from existing parts sold in the market has been assembled and tested. Estimated electrochemical reactions are discussed for initial charging process with Vanadium Pentoxide powder as initial state to obtain fully charged battery state with V2+ ion in anolyte and VO2 + ion in catholyte. Material corrosion testes were done by immersing the material in a Vanadium electrolyte and by using the material as a bipolar plate in the VRFB system. Immersion test showed that copper, steel, lead and zinc were corroded badly. In bipolar plate material test, stainless steel 316, aluminum and silver plates were corroded after some hours of electric charging process. Simple carbon plastic composites and 3-mm thickness graphite plates were tested in the bipolar plate material test and failed due to corrosion problem as well. In the VRFB prototype, corrosion problems occurred on brass nipples, polyurethane plastic pipes and porous silicone seals. Stronger plastic components and better quality of silicone seals are needed for VRFB. Significant finding of this study is possible spontaneous chemical reaction within anolyte tank as a potential of self-discharging reaction which other researchers have not identified. Also, another finding from this study is that good bipolar plate for VRFB is not easily available in the market.